2019
DOI: 10.1021/acs.jpcc.9b03025
|View full text |Cite
|
Sign up to set email alerts
|

CO-PROX Reaction over Co3O4|Al2O3 Catalysts—Impact of the Spinel Active Phase Faceting on the Catalytic Performance

Abstract: A series of α-alumina supported cobalt spinel catalysts of various exposition of the (100), (111) and (110) planes was synthetized and tested in CO-PROX reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…Several previous reports have demonstrated that the surface oxidation state of cobalt plays a key role for COPrOx reactivity. ,, At low temperatures, the COPrOx mixture can oxidize metallic cobalt, whereas at relatively high temperatures, cobalt oxides could be reduced back to metal. ,, Thus, depending on the COPrOx reaction conditions, cobalt may easily swap between different oxidation states. Herein, synchrotron-based NAP-XPS and NEXAFS were used to monitor, on a comparative basis, the surface oxidation state of CoO x and CoVO x during the COPrOx reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Several previous reports have demonstrated that the surface oxidation state of cobalt plays a key role for COPrOx reactivity. ,, At low temperatures, the COPrOx mixture can oxidize metallic cobalt, whereas at relatively high temperatures, cobalt oxides could be reduced back to metal. ,, Thus, depending on the COPrOx reaction conditions, cobalt may easily swap between different oxidation states. Herein, synchrotron-based NAP-XPS and NEXAFS were used to monitor, on a comparative basis, the surface oxidation state of CoO x and CoVO x during the COPrOx reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The temperature range also matches that generally observed for the reduction of the Co3O4 spinel phase. 32,33 It is thus attributed to the reduction of Co3O4 crystallites. In fact, the narrow profile is very similar to that of unsupported 3D Co3O4, 32,33 CoNO3/graphene, respectively.…”
Section: Characterization Of Graphene-supported Cobalt Oxides From Thmentioning
confidence: 99%
“…32,33 It is thus attributed to the reduction of Co3O4 crystallites. In fact, the narrow profile is very similar to that of unsupported 3D Co3O4, 32,33 CoNO3/graphene, respectively. The calcined CoNO3-derived composite exhibits a maxima at 380°C, which is similar to the calcined composite derived from the Pc route, with two shoulders at 330°C and 450°C.…”
Section: Characterization Of Graphene-supported Cobalt Oxides From Thmentioning
confidence: 99%
“…The spectra of Co 2p show two asymmetric peaks which can be assigned to Co 2p3/2 and Co 2p1/2 together with corresponding satellite structures. The deconvolution of these spectra revealed the presence of several overlapping features associated to Co 3+ (780.1 ± 0.6 and 795.4 ± 0.6 eV) and Co 2+ (781.7 ± 0.7 and 797.3 ± 0.7 eV) [53]. The observed satellite peaks are typical for spinel structures consists of 3+ cations occupy octahedral lattice sites, filled t 2g and empty e g levels, and 2+ cations in tetrahedral sites [54].…”
Section: Physicochemical Characterization Of Catalysts 321 Xrf Tgmentioning
confidence: 99%